INCIDENCE AND RISK FACTORS OF SURGICAL SITE INFECTION FOLLOWING CESAREAN SECTION IN A TERTIARY CARE CENTRE IN NORTH KERALA, INDIA - BH, HIBA HASHIM; T, HEERA SHENOY; VK, CHELLAMMA; ANTONY, ABHILASH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: To objectives of the study were to study 1) the incidence and maternal determinants (host related) risk factors on post cesarean surgical site infection (SSI) and 2) the influence of labor related and procedure related risk factors on post cesarean SSI. Methods: This study was conducted in the Department of Obstetrics and Gynaecology, KMCT Medical College, Kozhikode from April 1 to August 31 2021 after clearance from ethical committee in which 153 cases of SSI post cesarean were included in the study. Results: Educational status of patients had statistically significant association with the development of SSI incidence of SSI (44.4%) and is highest among overweight women. Patients with diabetes and hypertension had increased risk of developing SSI. 72.2% with SSI had duration of ruptured membrane for >8 h and duration of rupture of membrane were significantly associated with development of wound infection. Significant linear association was found between number of prior cesarean and risk of development of SSI (p=0.019). Cesarean with mean operative time >45 min had statistically significant risk of developing SSI. Intraoperative complication like adhesions was a predictor of SSI (p=0.001) Conclusions: Medical morbidities and increased body mass index being predictors along with prolonged operative time can be properly identified and awareness ensured to prevent and identify post cesarean SSI.